Conjure women : a novel - Atakora, Afia (Random House, an imprint and division of Penguin Random House LLC, 2020)
"Like her mother, Rue is an all-knowing midwife, healer, and conjurer of curses on the plantation of Marse Charles. Moving back and forth in time between the years before and after the Civil War, this novel tells the story of Rue, the families she cares for, and the mysteries and secrets she knows about the plantation owner's daughter, Varina. At the heart of this story is the intimate bonds and transgressions among people and across racial divides, during both slavery time and freedom time."--Publisher.